Inequality changes over time, pro-poor growth and reranking: local focus and global assessment - Bárcena-Martín, Elena María; Imedio-Olmedo, Luis J.; Parrado-Gallardo, Encarnación Macarena (XXI Encuentro de Economía Pública, 2014)
When measuring the change in inequality the conclusion based on an overall inequality measure can hide some important changes at different parts of the distribution. In this paper we propose the decomposition of the inequality change measured through a family of inequality measures proposed by Imedio et al. (2013) into measures of pro-poor income growth and reranking in the income pecking order. Moreover, making use of the result of Imedio et al. (2013) that shows that the Bonferroni index can be seen as the sum of inequality measures that give more weight to inequality in different parts of the income distribution (inequality measures with local focus) we propose a decomposition that reveal the extent to which each part of the income distribution contributes to the global measure of inequality, reranking and pro-poor growth. These results make the analysis of changes in inequality more insightful, as they help to evaluate the homogeneity of the change in inequality, reranking and pro-poor growth along the income distribution and enable to estimate the contribution of the “local” measures to the global one. We use this framework to analyze the effect of the crisis on employee income and self-employment income in 11 European countries.
Keywords: Desigualdad social; Desigualdad social - Modelos matemáticos; Bonferroni index; Inequality; Reranking; Pro-poor growth